ANALISIS FUNGSI PEMASARAN BUAH MANGGIS DI HUTAN RAKYAT DESA AIR KUBANG KABUPATEN TANGGAMUS - Annas Thasya Ningrum; Susni Herwanti; Hari Kaskoyo (Lambung Mangkurat University-Indonesia, 2020)
Community forests are forests that are built and managed by the community to support the economy. Community forests function in regulating water management, resisting farmers who are relatively small. The types of data used are primary data and secondary data. Data is analyzed in a qualitative descriptive. The results of the study show that the marketing institutions involved are village level collectors, district level collectors, district level wholesalers and retailers. Marketing functions conducted by marketing institutions is the function of exchange in the form of sales and purchase, physical functions of transport and storage and facility functions in the form of standarization, risk and market information.erosion and providing forest products for community needs. One of the plants that contributes in supporting the environment and generating economic value for the community is mangosteen (Garcinia mangostana). In mangosteen marketing, the amount of costs incurred by the marketing institutions involved will cause the greater price difference between farmers and consumers. The purpose of this study is to determine the marketing functions performed by the mangosteen marketing agency. Data collection is done by observation, interview and literature study. Sampling was conducted by census in order to examine the entire population of mangosteen